2023
DOI: 10.3390/plants12112130
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Zinc Oxide Nanoparticles Using Viscum album Extracts: Unveiling Bioactive Compounds, Antibacterial Potential, and Antioxidant Activities

Abstract: The current study explored the antioxidant and antibacterial capabilities of zinc oxide nanoparticles (ZnONPs) synthetized using methanolic leaf extracts of the medicinal herb Viscum album. Through TEM investigation and UV–Vis analysis, which peaked at 406 nm, the synthesis of ZnONPs was verified. TEM analyses showed that the synthesized ZnONPs had a size distribution with an average of 13.5 nm and a quasi-spherical shape. Forty-four phytoconstituents were found in the methanolic leaf extracts of V. album. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Rini et al reported a green method of synthesizing ZnO nanoparticles using pineapple-peel extract and evaluated their antibacterial activity [11]. Moreover, almond shells, sugar cane bagasse, eggshells, Viscum album leaves, peppermint tea dregs, marine brown algae, and many plant extracts have been used for the synthesis of ZnO nanoparticles [12][13][14][15]. Hence, the green synthesis approach to obtaining ZnO nanoparticles has significant potential for further exploration and development.…”
Section: Introductionmentioning
confidence: 99%
“…Rini et al reported a green method of synthesizing ZnO nanoparticles using pineapple-peel extract and evaluated their antibacterial activity [11]. Moreover, almond shells, sugar cane bagasse, eggshells, Viscum album leaves, peppermint tea dregs, marine brown algae, and many plant extracts have been used for the synthesis of ZnO nanoparticles [12][13][14][15]. Hence, the green synthesis approach to obtaining ZnO nanoparticles has significant potential for further exploration and development.…”
Section: Introductionmentioning
confidence: 99%
“…Several plant extracts have been widely used for the biosynthesis of ZnO NPs, such as: Andrographis paniculate [12], myristica fragrans [13], Plumbago auriculata Lam. [14], Cayratia pedate [11], Origanum majorana [2], Psidium guajava [8], Zingiber o cinale & Allium sativum [15], green algae [16], dan Viscum album [17].…”
Section: Introductionmentioning
confidence: 99%